2020
DOI: 10.21203/rs.3.rs-85394/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Control to Elimination: A Spatial-Temporal Analysis of Malaria Along the China-Myanmar Border

Abstract: Background: Malaria cases have declined significantly along the China-Myanmar border in the past 10 years and this region is going through a process from control to elimination. The aim of this study is to investigate the epidemiology of malaria along the border, will identify challenges in the progress from control to elimination. Methods: National reported malaria cases from China and Myanmar, along with the data of 18 Chinese border counties and 23 townships in Myanmar were obtained from a web-based disease… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In the last three years of the study period, P. vivax clustered in eastern Kachin State bordering China and southern Shan State and Kayah State bordering Thailand. Previous studies showed P. vivax is the predominant species along many of these international borders [25,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In the last three years of the study period, P. vivax clustered in eastern Kachin State bordering China and southern Shan State and Kayah State bordering Thailand. Previous studies showed P. vivax is the predominant species along many of these international borders [25,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…These challenges have led to the emergence of geographically-based initiatives to tackle malaria in border regions [23,[101][102][103]. The Elimination Eight Initiative (E8) (https:// malar iaeli minat ion8.…”
Section: Malaria Among Angola's Neighbours and The Elimination Eight ...mentioning
confidence: 99%
“…5) [104]. The E8 is pioneering an ambitious regionally-based strategy including cross-border initiatives to roll back malaria from the southernmost countries, including Angola, and accelerate collective progress towards zero transmission [103,104]. As part of E8 initiatives, eight border malaria health posts and surveillance teams were deployed to the border areas of the provinces of Cuando Cubango and Cunene, where "Test, Treat and Track" (TTT) measures were implemented, providing access to malaria diagnosis and treatment services, specifically targeting two key populations at risk of malaria, namely underserved residents of border districts, and mobile and migrant populations.…”
Section: Malaria Among Angola's Neighbours and The Elimination Eight ...mentioning
confidence: 99%